2023
DOI: 10.3389/fpsyt.2022.1040023
|View full text |Cite
|
Sign up to set email alerts
|

Integrating technology in mental healthcare practice: A repeated cross-sectional survey study on professionals’ adoption of Digital Mental Health before and during COVID-19

Abstract: As a consequence of the outbreak of the COVID-19 global pandemic in the spring of 2020, large-scale social distancing measures were implemented, resulting in the forced adoption of online or digital forms of psychological treatment. This sudden transition to digital care offered a unique opportunity to investigate if and how this experience impacted mental healthcare professionals’ perceptions and use of Digital Mental Health tools. The current paper presents findings of a repeated cross-sectional study consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The clinicians in this study indicated that TMH was most useful when used in combination with face-to-face interactions and for the continuity of care and maintenance of recovery. The role and usefulness of TMH as an adjunct to face-to-face care have also been reported by other authors [45][46][47].…”
Section: Discussionsupporting
confidence: 69%
“…The clinicians in this study indicated that TMH was most useful when used in combination with face-to-face interactions and for the continuity of care and maintenance of recovery. The role and usefulness of TMH as an adjunct to face-to-face care have also been reported by other authors [45][46][47].…”
Section: Discussionsupporting
confidence: 69%
“…For example, it may help to increase interpersonal synchrony in a therapeutic setting (Fiskum, 2019) or promote empathy and social entrainment between two people (Tennant et al, 2019). Besides heart rate variability, skin conductance has been used to provide (simulated) dyadic feedback (Feijt et al, 2020) and other studies have provided ANS-based biofeedback based on breathing rhythm (Järvelä et al, 2019;Stepanova et al, 2020;Salminen et al, 2022). Popular feedback modalities in this context are pure visual (Feijt et al, 2020), or auditory feedback (Tennant et al, 2019) as well as a multisensorial approach via virtual realities (Järvelä et al, 2019;Stepanova et al, 2020;Salminen et al, 2022).…”
Section: Ans-based Biofeedback and Hormonal Manipulationsmentioning
confidence: 99%
“…A recent study (Feijt et al, 2023) added that the forced use of digital technologies to deliver fully remote psychological services during the COVID-19 pandemic positively changed the perception of psychologists about digital mental health but did not change their perception of proficiency and/or readiness to use it. Despite the increase in the use and perceived value of digital technologies for the provision of psychological services, most psychologists reported the intention to use it in a blended approach (Feijt et al, 2023). Another study (Mendes-Santos et al, 2022) points in the same direction, with mental healthcare professionals increasing the use of digital technologies to provide remote services, although considering that the absence of validated interventions and structured training programs, among others, limits their adoption of this modality in their daily practice.…”
mentioning
confidence: 99%
“…This aspect might have contributed to the disruption most countries reported in mental health services (World Health Organization, 2020; 2021). Furthermore, although most psychologists resorted to digital technologies to provide fully remote mental health services during COVID-19 lockdowns, the lack of knowledge and training on using digital technologies for clinical purposes inhibited their sustained adoption post-confinement (Dores et al, 2020; Feijt et al, 2023). Psychologists reported technological (i.e., more related to the interaction between the professional and the technical devices), clinical (i.e., limitations in approaching some topics therapeutically), safety, and privacy-related concerns, and underlined the importance of accessing clear guidelines on the provision of remote psychology services to pursue such a practice (Dores et al, 2020; Mendes-Santos et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation